Penyuluhan Hukum Pencegahan Tindak Pidana Narkotika di Kelurahan Winduherang, Kuningan - Abi Wisnu Rahmatullah; Fauzan Alkautsar; Heri Ramdani; Indah Tri Utami; Karolina Maulida; M Hanifan Bagus P; Susi Anjas Astuti; Suwari Akhmaddhian; Iman Jalaludin Rifai; Dikha Anugrah (Empowerment : Jurnal Pengabdian Masyarakat, 2025)
Teenagers are thefuture generation of a nation whose mindset and social association must be protected and guided. They can threaten the futureof a nation when they are not well directed anymore. Nowadays, teenagers are threatened by drug abuse, ana ddictivething which influences immune system, emotion, mindset, and reason. Teenage drug a busers could be increased in annually, there foreanunder standing of what lies behind it is needed. One of several factors believed to be the background of druga bused by teen agersisp sychological well-being. Based on these problems, legal guidance and legal counseling among adoescents need to be carried out sothatado lescents can better understand and have deterrence against drugs. The approach method used in this dedication activity to the community is in the form of legal counseling about preventing drug abuse and a participatory approach, meaning that participants are required to be active in participating throughout the activity.